The Role of The Internet of things in Healthcare Transformation - Sardar M. N. Islam (International Transactions on Artificial Intelligence, 2023)
The internet of things (IoT) must now be enhanced in the eraof the industrial revolution 4.0 to simplify healthcare andincrease its effectiveness in monitoring patients' healthconditions remotely.The Internet of Things (IoT) is a globalnetwork of interconnected computing devices that includespeople, machines, and other living things. Each of thesedevices has been given a unique identifier and has the abilityto send and receive data over the network without the need fordirect human or machine-to-human communication.Connectivity, standards, smart analytics, smart actions,networks, sensors, smart analytics, devices, cloud, and userinterfaces are some of the elements of the Internet of Things.IoT transformation in personal healthcare can be classifiedinto in-clinic care and remote monitoring. IoT security systemsand patient data protection must be carefully considered toprevent data leakage or improper processing of health dataobtained through the use of IoT. To make the most of IoT, thegrowth of IoT in the healthcare industry must be matched bylaws and regulations governing personal data security.